Risk assessment in pulmonary arterial hypertension. Issue 3 (29th March 2018) - Hoeper, Marius M.; Pittrow, David; Opitz, Christian; Gibbs, J. Simon R.; Rosenkranz, Stephan; Grünig, Ekkehard; Olsson, Karen M.; Huscher, Doerte
In its August 2017 issue, the European Respiratory Journal published two papers on risk assessment in pulmonary arterial hypertension (PAH), one coming from the French registry [1], the other from COMPERA, a European pulmonary hypertension (PH) registry [2]. Both groups utilised abbreviated versions of the risk assessment strategy proposed in the current European PH guidelines [3, 4] and both included basically the same variables, i.e. World Health Organization functional class (FC), 6-min walking distance (6MWD), cardiac index, right atrial pressure and serum levels of brain natriuretic peptide (BNP) or the N-terminal fragment of its propeptide (NT-proBNP). In both studies, the cut-off values used to determine risk were those proposed in the European guidelines [3, 4]. However, the strategy to determine individual risk differed in the two studies: COMPERA calculated the average individual risk by assigning a score of 1, 2 or 3 to each criterion (1: low risk; 2; intermediate risk; 3: high risk) and rounding to the mean of the available variables, as had been previously proposed by a group from Sweden [5]. The French group, in contrast, looked at the number of variables that met the low-risk criteria. Despite these differences, the main results of both studies were similar, especially 1) that the risk stratification tool proposed by the European guidelines adequately predicted mortality, 2) that follow-up risk assessment on treatment was a more reliable predictor of survival than the initial risk assessment at the time of diagnosis, and 3) that FC, 6MWD and BNP/NT-proBNP at follow-up were independent predictors of outcome. However, there also were important differences in the two analyses: in the French study, 19% of the patients with idiopathic PAH (IPAH) met all three noninvasive low-risk criteria at follow-up, i.e. FC I or II, 6MWD >440 m, BNP <50 ng·L −1 or NT-proBNP <300 ng·L −1 ; these patients had a 1-year survival of 100% and a 5-year survival of 97%. In COMPERA, 21% of the IPAH patients were classified as low risk at follow-up; these patients had a 1-year survival of 96% but the 5-year survival of these patients was only 72% (data available in the online supplement of [2]). We wondered whether the differences in long-term survival were due to the fact that the low-risk definition was less strict with the COMPERA strategy than with the French strategy or whether differences in the two patient cohorts were responsible for these findings (patients in French cohort were younger than the patients in COMPERA and combinations of PAH drugs were used more frequently in the French series than in the COMPERA cohort). PAH patients reaching a low risk profile with targeted therapies have an excellent long-term survival http://ow.ly/RBjo30i6N57